Peripheral blood CD163(+) monocytes and soluble CD163 in dry and neovascular age‐related macular degeneration. Issue 6 (25th April 2020) - Daftarian, Narsis; Zandi, Souska; Piryaie, Golbarg; Nikougoftar Zarif, Mahin; Ranaei Pirmardan, Ehsan; Yamaguchi, Muneo; Behzadian Nejad, Qurban; Hasanpour, Hossein; Samiei, Shahram; Pfister, Isabel B.; Soheili, Zahra‐Soheila; Nakao, Shintaro; et al.
Abstract: Macrophages are the main infiltrating immune cells in choroidal neovascularization (CNV), a hallmark of the human wet, or neovascular age‐related macular degeneration (AMD). Due to their plasticity and ability to adapt to the local microenvironment in a tissue‐dependent manner, macrophages display polar functional phenotypes characterized by their cell surface markers and their cytokine profiles. We found accumulation of hemoglobin‐scavenging cluster of differentiation 163 (CD163)(+) macrophages in laser‐induced CNV lesions and higher expression of CD163(+) monocytes in the peripheral blood on day 7 post injury in mice. In comparison, CD80(+) macrophages did not differ with laser‐injury in young or aged mice and did not significantly change in the peripheral blood of CNV mice. We examined the percentages of CD163(+), CD206(+), and CD80(+) monocytes in the peripheral blood of patients with wet AMD, patients with dry AMD, and in age‐matched individuals without AMD as controls. Percentages of peripheral blood CD163(+) monocytes in both dry AMD ( P  < .001) and wet AMD ( P  < .05) were higher than in age‐matched non‐AMD controls, while there was no difference between the groups in the percentages of peripheral CD206(+) and CD80(+) monocytes. Further, serum level of soluble CD163 (sCD163) was elevated only in patients with wet AMD ( P  < .05). An examination of 40 cytokine levels across the study groups revealed that anti‐VEGF treated patients with wet AMD, who showed no exudative signs on the day of blood drawing had a cytokine profile that was similar to that of non‐AMD individuals. These results indicate that CD163 could be further evaluated for its potential as a useful marker of disease activity in patients with neovascular AMD. Future studies will address the origin and potential mechanistic role of CD163(+) macrophages in wet AMD pathologies of angiogenesis and leakage of blood components.